Economic Evaluation of Posaconazole Versus Standard Azole Therapy as Prophylaxis against Invasive Fungal Infections in Patients with Prolonged Neutropenia in Canada - Amir A Tahami Monfared; Amy K O’Sullivan; Coleman Rotstein; George Papadopoulos (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Posaconazole prophylaxis in high-risk neutropenic patients prevents invasive fungal infection (IFI). An economic model was used to assess the cost effectiveness of posaconazole from a Canadian health care system perspective.